Effect of integrated nutrient management on productivity, nutrient removal and soil quality of rainfed upland rice in north east India - Borah, D; Ghosh, M; Ghosh, D C; Gohain, T (ORYZA-An International Journal of Rice, 2019)
A field experiment was conducted to evaluate the effect of chemical fertilizers, farm yard manure (FYM), vermicompost (VC), biofertilizer and their combinations on productivity, nutrient removal and nutrient use efficiency of rainfed upland rice and its impact on soil health. The experiment was laid out in randomized complete block design (RCBD) with direct sown upland rice. The results showed that integrated use of 75% recommended dose of nitrogen (RDN) through FYM or VC + 25% recommended dose of fertilizers (RDF)produced higher grain (3.49 t ha-1)and biomass (10.25 t ha-1) yield, recorded higher nutrient removal (80.1, 28.65 and 114.5 kg ha-1 N, P and K,  respectively) and greater nutrient use efficiency (15.6 kg kg-1) than thoseof other nutrient management practices. It increased grain yield by 1.65 t ha-1 (89.6%) over control and 0.80 to 0.92 t ha-1 (29.9 to 35.6%) over other treatments. It also improved physico-chemical properties of the experimentalsoil after two years of rice cropping in spite of greater removal of plant nutrients over other treatments except only organic manuring (100% RDN through FYM or VC).This experiment established that integrated nutrient management (INM) with 75% RDN through FYM or VC + 25% RDF was helpful for increasing crop productivity, improving nutrient use efficiency and soil quality of rainfed uplands necessary for sustainable productivity.